2015
DOI: 10.1111/1754-9485.12302
|View full text |Cite
|
Sign up to set email alerts
|

Radioguided occult lesion localisation using iodine‐125 seeds (‘ROLLIS’) for removal of impalpable breast lesions: First Australian experience

Abstract: ROLLIS is an easily learnt, safe and effective alternative technique to standard HWL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…16 However, the seed is a sealed source of radioactivity and careful compliance with state licensing regulations, staff training and strict use of protocols are required to minimize any risk of seed loss. 17 Our initial study confirmed ROLLIS is an easily learned, safe and effective alternative technique to HWL. 17 The purpose of the extended ROLLIS pilot study was to confirm the feasibility of using lower activity seeds in routine clinical settings with large numbers of multidisciplinary staff, in preparation for a randomized clinical trial (ANZCTR: 347672, UTN: U1111-1127-4903).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…16 However, the seed is a sealed source of radioactivity and careful compliance with state licensing regulations, staff training and strict use of protocols are required to minimize any risk of seed loss. 17 Our initial study confirmed ROLLIS is an easily learned, safe and effective alternative technique to HWL. 17 The purpose of the extended ROLLIS pilot study was to confirm the feasibility of using lower activity seeds in routine clinical settings with large numbers of multidisciplinary staff, in preparation for a randomized clinical trial (ANZCTR: 347672, UTN: U1111-1127-4903).…”
Section: Introductionsupporting
confidence: 60%
“…Previous trials have confirmed that seed localization is safe and staff radiation doses are negligible . However, the seed is a sealed source of radioactivity and careful compliance with state licensing regulations, staff training and strict use of protocols are required to minimize any risk of seed loss …”
Section: Introductionmentioning
confidence: 99%
“…According to Pavlicek et al 23 , the maximum dose deposited in the residual breast that received the seed implant is rather low, around 2 cGy, equivalent to the dose of two X-ray incidences of a routine mammography. A survey on the amount of radiation received by the surgical team showed that no one received a dose higher than the environmental level 24 , proving the absence of risk to the medical staff, to the patient and to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Following our experience with ROLL, we performed a pilot study where a low activity iodine-125 seed and a back-up hookwire were inserted into impalpable breast lesions using ultrasound or stereotactic guidance (Radioguided Occult Lesion Localisation using Iodine 125 Seeds, “ROLLIS”). 3 The seeds are 0.8 × 4.5 mm radiopaque titanium cylinders containing ∼ 2 MBq of I-125 adsorbed onto a silver wire. The energy emitted by I-125 (27 keV) differs significantly from that emitted by the Tc-99m used for sentinel node mapping (140 keV).…”
mentioning
confidence: 99%
“…Several studies have reported improved margin status and re-excision rates for ROLL and ROLLIS compared with hookwire localisation 3 however ROLLIS has advantages over ROLL: I-125 seeds are radiopaque, allowing easy confirmation of placement accuracy on pre-operative mammography. Unlike hookwires and the liquid form of tracer used in ROLL, I-125 seeds rarely migrate after insertion, providing a stable point source of radioactivity for precise lesion localisation.…”
mentioning
confidence: 99%